Achieving biological nutrient removal in an old sewage treatment plant through process modifications – A simulation and experimental study. (February 2022) - Mohan T, Reshma; Chanakya, H.N.; Mohan Kumar, M.S.; Rao, Lakshminarayana
Abstract: Modifying old sewage treatment plants (STP) to meet revised stringent discharge standards is of great concern. Process modeling can serve as an essential tool for this. This work reports a BioWin©-activated sludge model/anaerobic digestion for a 55 million litres per day STP located in South India. Fifty state variables and eighty process equations were used in the model to achieve biological nutrient removal. The model was calibrated and was validated with plant data. The proposed modification was to incorporate an intermediate virtual anoxic zone to achieve simultaneous nitrification-denitrification and total dissolved phosphorus (TDP as PO4 ) removal. Several scenarios, namely, different hydraulic residence time (HRT) between 1.5 to 2.5 h, dissolved oxygen (DO) between 2.5 to 4.5 mg/L, and mixed liquor suspended solid (MLSS) between 2500 to 4500 mg/L in the bioreactor, were studied to identify optimum conditions. The optimum DO and MLSS levels were identified as 4 mg/L and 4000 mg/L, respectively. The optimum HRT of 2 h in aeration zone, 1 h in anoxic, and 3 h in reaeration zone was identified. Implementation of these modifications in the STP, with minimal operational interventions and no capital costs, improved its performance as predicted by the model. The total nitrogen and TDP (as PO4 ) reduced from 20 mg/L to 8 mg/L and 3.5 mg/L to 0.9 mg/L, respectively, and met the revised discharge standards. This intervention gave a cost saving of approximately 5.6 million USD. Graphical abstract: Unlabelled Image Highlights: Process modifications was proposed to achieve biological nutrient removal. Optimum dissolved oxygen was identified as 4 mg/L. Optimum mixed liquor suspended solid was identified as 4000 mg/L. Total nitrogen and dissolved phosphorous were 8 and 1 mg/L in treated water. This intervention gave a capital saving of $ 5.6 million and avoided plant shutdown.